The ecuadorian military intelligence in the risk society - Ordóñez, María Dolores (2017)
Development and new lectures regarding world’s current risks compel us to reconfigure the role of military institutions and, therefore, their purpose regarding intelligence. The transition from modernity to new forms that would exceed its postulates , in which societies are summited to the logics of market and bureaucracy, as well as the analysis about risks and security are not always related to the conditions that could be considered a threat to human life, but also to governability, economic stability, public opinion, among other problems. From the perspective of Anthony Giddens and Ulrich Beck, there will be a reflection about the dimensions that must be considered by military intelligence of contemporary army forces, adjusted to realities where the “abstract systems” dominate and demand the development of a strategic intelligence that doesn’t constrict itself to cover national and territorial sovereignty issues only. In order to achieve this there will be an examination of nowadays priorities for the military intelligence of Ecuador and the necessity to reinvent itself during the transition from a traditional to a global outline, moreover, when they have to act in this risk context, with sources that do not adjust to this reality, since the scientific-technological capacity and, therefore, the intelligence doctrinal conceptions, are not still inscribed in the globalizing dynamics.